2013
DOI: 10.1039/c3an36696k
|View full text |Cite
|
Sign up to set email alerts
|

An on-line push/pull perfusion-based hollow-fiber liquid-phase microextraction system for high-performance liquid chromatographic determination of alkylphenols in water samples

Abstract: In this study, we employed a novel on-line method, push/pull perfusion hollow-fiber liquid-phase microextraction (PPP-HF-LPME), to extract 4-tert-butylphenol, 2,4-di-tert-butylphenol, 4-n-nonylphenol, and 4-n-octylphenol from river and tap water samples; we then separated and quantified the extracted analytes through high-performance liquid chromatography (HPLC). Using this approach, we overcame the problem of fluid loss across the porous HF membrane to the donor phase, permitting on-line coupling of HF-LPME t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…At the beginning of 2013, our group developed a rapid on-line HF-LLLME system operating in ow-through mode-so-called the ultrasoundassisted push/pull perfusion HF-LLLME (UA-PPP-HF-LLLME). 9,10 We found that the extraction efficiency of target analytes when using on-line HF-LLLME in the ow-through mode was highly dependent on the perfusion mode, possibly because of leakage of the acceptor phase uid across the porous HF membrane. Further efforts will be required to clarify this assumption.…”
Section: Introductionmentioning
confidence: 90%
“…At the beginning of 2013, our group developed a rapid on-line HF-LLLME system operating in ow-through mode-so-called the ultrasoundassisted push/pull perfusion HF-LLLME (UA-PPP-HF-LLLME). 9,10 We found that the extraction efficiency of target analytes when using on-line HF-LLLME in the ow-through mode was highly dependent on the perfusion mode, possibly because of leakage of the acceptor phase uid across the porous HF membrane. Further efforts will be required to clarify this assumption.…”
Section: Introductionmentioning
confidence: 90%
“…The 25-μL HPLC syringe served to introduce the acceptor solution into the HF prior to extraction and to collect this solution after extraction, while the conventional medical syringe needle was used to support the HF. Although the assistance of PPP and ultrasonication makes UA-PPP-HF-LPME a rapid and efficient approach for on-line extraction of acidic analytes featuring ionizable functionalities, 10,11 we have limited information regarding the effects of both PPP and ultrasonication on the stability of the extraction solvent or its extraction capability, including extraction speed, toward neutral compounds. On the other hand, although ultrasonic radiation is a powerful tool that can accelerate various steps during sample pretreatment, our understanding of its interaction effects with other effective HF-LPME variables remains limited.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…By using an ultrasonic probe and a push/pull syringe pump to accelerate the mass transfer and dispense the acceptor phase to the HF, the optimized extraction time for the extraction of acidic phenols from water samples decreased to only 2 min, with enrichment factors (EFs) from 82 to 279. 10,11 The on-line coupling of a regular HF-LPME device requires two important factors to be considered: (i) the thick contact wall of the HF will potentially necessitate long extraction times, which would result in low sample throughput in on-line applications, for target analytes; and (ii) the acceptor-to-donor/ donor-to-acceptor fluid pressure caused by the flowing acceptor phase stream in the HF lumen can potentially lead to fluid loss or fluid gain across the porous membrane, thereby decreasing the collection of the extracted acceptor phase or diluting the extracted acceptor phase. 10,11 Although a few papers describe the problem, 10,11 none have reported the extent of inner-fiber fluid leakage in HF-LPME (especially for HF-LPME in nonstatic modes, such as dynamic HF-LPME and on-line HF-LPME); nevertheless, some suspected SLM leakage has been found in previous studies of nonstatic HF-LPME.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Using liquids in the core of a bicomponent fiber can add new characteristics to the fibers applications. There are a large number of studies reporting optical, self‐healing, and membrane applications of liquid‐filled fibers. Xu et al .…”
Section: C/s Fibersmentioning
confidence: 99%